2022
DOI: 10.1021/acs.cgd.2c01017
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir Form III: A Coincidental Concurrent Discovery

Abstract: Polymorph screening is a crucial step in the characterization and development of pharmaceuticals. The 1998 recall of ritonavir upon the unexpected appearance of the more stable Form II polymorph remains a notorious case of disappearing polymorphs as the presence of Form II inhibited the ability to grow the original Form I. This study presents the characterization of Form III of ritonavir grown from melt/cool crystallization. While Form III was observed in 2014, it was not characterized as a unique polymorph un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…High-throughput polymorph screening by Morissette et al 8 revealed (see Table 1) the existence of two new solvates (forms IIIa and V) as well as a further (metastable) phase (form IV), but up to now their full crystal structures have not been reported, albeit recent work 9 through melt crystallisation has now resulted in a further solid form with its crystal structure (form IIIb, 10 see Table 1). In this respect, due to the form III nomenclature being claimed for both the form identified from screening 8 and that recently crystallised from the melt, 9 for clarity we have referred to these two structures herein after as forms IIIa and IIIb, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput polymorph screening by Morissette et al 8 revealed (see Table 1) the existence of two new solvates (forms IIIa and V) as well as a further (metastable) phase (form IV), but up to now their full crystal structures have not been reported, albeit recent work 9 through melt crystallisation has now resulted in a further solid form with its crystal structure (form IIIb, 10 see Table 1). In this respect, due to the form III nomenclature being claimed for both the form identified from screening 8 and that recently crystallised from the melt, 9 for clarity we have referred to these two structures herein after as forms IIIa and IIIb, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This project was launched in early 2020, but regrettably, obtaining insufficient data due to COVID-19 until now. During our research, two labs reported the discovery of RIT Form III, and gave the crystallographic parameters by SCXRD or PXRD indexing, both of which are similar to our results solved from the data collected using a laboratory diffractometer ( C 2 space group and Z ′ = 1 with a significantly serious disorder, Figure S1). One of the most significant differences between the synchrotron structure and the in-house device structure is Z ′, the number of conformations in the asymmetric unit.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, as mentioned by Parent et al, the PXRD pattern of Form III has been reported in 2014 but was erroneously identified as Form IV . The melt microdroplet strategy for single crystal cultivation and synchrotron radiation for data collection together enabled the correct structure elucidation and complete identification of this new phase.…”
Section: Discussionmentioning
confidence: 98%
“…However, the possibility that form I is favored kinetically but not thermodynamically is supported by experimental observations, such as the frequent omission of molecules of H 2 O and the associated rapid growth of crystals along the a - and b -axes. If so, form I of pitolisant hydrochloride is vulnerable to being supplanted by the appearance of a more stable form, as in the notorious case of ritonavir. The CSP results (Figure ) suggest the structures of several potential lower-energy polymorphs.…”
Section: Resultsmentioning
confidence: 99%